KAJIAN MIMESIS SOSIAL SEBAGAI CERMIN KEHIDUPAN MASYARAKAT DALAM CERPEN “LAKI-LAKI TUA TANPA NAMA” KARYA BUDI DARMA - Ridho Sastro Panjaitan; Intan Valiza; Mika Charolin; Mesya Fadila Sani Harahap; Ledy Novwanty Nainggolan; Tomi Arianto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to explain how forms of social mimesis emerge in Budi Darma's short story "Orang Tua Tanpa Nama" (Old Man Without a Name) and to describe how social reality is represented in the story. The method used in this study is qualitative, with a sociology of literature approach and social mimesis theory. The research data were obtained through literary studies and a close reading of short stories in the collection "Bloomington People" (1980). For data analysis, the Miles and Huberman model was used, consisting of three stages: data reduction, data presentation, and conclusion drawing. The results show that this short story displays four main forms of social mimesis: the alienation and marginalization of the main character, imbalances in power relations, collective indifference, and dehumanization in modern society, as well as the narrative strategies used by the author to emphasize social criticism. These findings indicate that Budi Darma's work not only depicts social reality but also contains a critique of society's increasingly individualistic and heartless life.